Integration of Beneficiaries of International Protection into the Labour Market: policies and practices in Ireland - Gusciute, Egle; Arnold, Samantha; Quinn, Emma (ESRI, 2016)
This study investigates and maps supports which aim to facilitate the integration of beneficiaries of international protection into the Irish labour market. We examine what employment-related support measures are available to beneficiaries, and the extent to which these are targeted to the needs of the group. The study finds that Ireland has not developed a system of labour market integration supports, tailored to the needs of refugees. Access by refugees to mainstreamed employment supports is unrestricted. However the provision of targeted integration measures is important because refugees can face specific barriers to participation, including: experiences of trauma, the absence of a social network, gaps in employment and education, and a lack of documentation hindering the recognition of qualifications by employers. Refugees can face also challenges in navigating the system of mainstream service provision. The report is based on the Irish contribution to an EU-level, European Migration Network (EMN) study on Integration of beneficiaries of international/humanitarian protection into the labour market: policies and good practices in the EU, the synthesis report of which compiles 24 country studies.